Analytical Model to Predict Residual Flexural Capacity of Recycled Aggregate Concrete Beams with Corroded Longitudinal Rebars - Zhenghao Zou; Guojiao Yang; Tian Su (Advances in Materials Science and Engineering)
This paper presents the results of research on the flexural behavior of recycled aggregate concrete (RAC) beams. The correlation between flexural behavior and the corrosion level of longitudinal rebar was analysed. Based on theoretical analysis and experiment results, the influence of corrosion on flexural cracking moment was analysed and a model to predict the residual flexural capacity of RAC beams with corroded longitudinal rebars was established. The experimental results show that the development degree of cover cracks deepens with the increase of the corrosion level, and the experimental data also demonstrate that the strain distribution of concrete in the midspan of beams conforms to the plane section assumption better when the corrosion level is little but no longer satisfies the plane section assumption when the corrosion level is high.